2010
DOI: 10.3109/17453671003619003
|View full text |Cite
|
Sign up to set email alerts
|

Early full weight bearing is safe in open-wedge high tibial osteotomy

Abstract: Background and purpose In open-wedge, valgus osteotomy of the upper tibia, there are concerns regarding the initial stability and ability to retain the correction. Rehabilitation protocols vary depending on the osteotomy technique and the fixation method. Angle-stable implants offer superior initial stability. Early full weight bearing appears to be possible using these implants. In this prospective cohort study, we measured migration in open-wedge osteotomy in patients following an early full weight bearing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 17 publications
3
69
0
4
Order By: Relevance
“…Nevertheless, high tibial osteotomy (HTO) has undergone somewhat of a resurgence in popularity over the last ten years due to the greater number of sports injuries with an increase in the frequency of arthrosis in young people [1]. The improvement in surgical technique [2,22], preservation of proximal tibial bone stock with medial opening wedge techniques [11] and advances in technology [3,7,16,17,24] allowing earlier range of motion and partial weightbearing [4] have all played a significant part. However, in most series with locked plate and screws, the majority of authors allow only partial weight-bearing with crutches.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, high tibial osteotomy (HTO) has undergone somewhat of a resurgence in popularity over the last ten years due to the greater number of sports injuries with an increase in the frequency of arthrosis in young people [1]. The improvement in surgical technique [2,22], preservation of proximal tibial bone stock with medial opening wedge techniques [11] and advances in technology [3,7,16,17,24] allowing earlier range of motion and partial weightbearing [4] have all played a significant part. However, in most series with locked plate and screws, the majority of authors allow only partial weight-bearing with crutches.…”
Section: Introductionmentioning
confidence: 99%
“…La deformidad angular en varo que afecta el compartimento tibiofemoral medial, es considerada por algunos autores como el sitio de inicio más común de la GP con evolución rápida de la enfermedad y es un factor a considerar en relación a la respuesta limitada de varias formas de tratamiento [49][50][51] .…”
Section: Consideraciones Del Tratamientounclassified
“…However, in 2006, van der Krans et al (10) observed nonunion after using a tricalcium phosphate (TCP) block in an adult male weighing 110 kg. Although bone graft substitutes have been successfully used in around-the-knee osteotomies (19)(20)(21), few foot and ankle surgeons recognized their value as block bone grafts until the mid-2010s because of the graft's structural fragility (10,18,22).…”
mentioning
confidence: 99%